Influence of seasonal mesoscale and microscale meteorological conditions in Svalbard on results of monitoring of long-range transported pollution [poster] - Dekhtyareva, Alena; Holmén, Kim; Maturilli, Marion; Hermansen, Ove; Graversen, Rune (UiT the Arctic University of Norway, 2018)
The Zeppelin Observatory is an atmospheric monitoring station located on the northwest coast of Spitzbergen island, in the Svalbard archipelago. The station provides background air composition, meteorological and climatological data for numerous research projects. The observatory is located on a mountain ridge in a region with complex topography that affects local atmospheric circulation processes. Research question: How the seasonal data collected at the Zeppelin observatory and Ny-Ålesund station (Fig. 2b), a temporarily station in the settlement, is affected by: 1) micrometeorological conditions 2) mesoscale dynamics 3) local air pollution